Management Science Applications in Tourism and Hospitality. - Gu, Zheng (Taylor and Francis, 2014)
Find out how accurate forecasting and analysis can prevent costly mistakes! Management Science Applications in Tourism and Hospitality examines innovative tools for evaluating performance and productivity in tourism offices, hotels, and restaurants. This collection of recent studies focuses on two important topics of management science: forecasting and a relatively new analytical methodology called data envelopment analysis (DEA). This book will show you how tourism forecasting accuracy can be enhanced and how DEA can be used to benchmark productivity and improve advertisement efficie.